2020
DOI: 10.1038/s41598-020-77982-3
|View full text |Cite
|
Sign up to set email alerts
|

Blattella germanica displays a large arsenal of antimicrobial peptide genes

Abstract: Defence systems against microbial pathogens are present in most living beings. The German cockroach Blattella germanica requires these systems to adapt to unhealthy environments with abundance of pathogenic microbes, in addition to potentially control its symbiotic systems. To handle this situation, four antimicrobial gene families (defensins, termicins, drosomycins and attacins) were expanded in its genome. Remarkably, a new gene family (blattellicins) emerged recently after duplication and fast evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…By extending recent in silico characterization of the innate immune repertoire of B. germanica ( Silva et al, 2020 ) in a functional direction, the work reported here provides new insight into the immunological adaptation of cockroaches to life in septic environments as well as the factors that regulate bacterial pathogen transmission by these insects.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…By extending recent in silico characterization of the innate immune repertoire of B. germanica ( Silva et al, 2020 ) in a functional direction, the work reported here provides new insight into the immunological adaptation of cockroaches to life in septic environments as well as the factors that regulate bacterial pathogen transmission by these insects.…”
Section: Discussionmentioning
confidence: 77%
“…Recent in silico analyses of the genomes of two synanthropic cockroach species, the American cockroach, Periplaneta americana , and the German cockroach, B. germanica, revealed an intriguing aspect of their immune systems ( Li et al, 2018 ; Silva et al, 2020 ). That is, when compared to distantly related holometabolous insects such as fruit flies and mosquitoes, both species encode an expanded arsenal of genes involved in the recognition and elimination of microbes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A screening of AMP gene expression in B. germanica transcriptomic projects available in the NCBI database, corresponding to 28 whole-body samples from different developmental stages, tissues and body parts, confirmed that some AMPs are expressed specifically in some developmental stage [119]. In fact, the expression of the novel blattellicins is restricted to adult females, although the tissue in which they are expressed is unknown.…”
Section: Role Of the Host Immune System In The Symbiotic Interactionmentioning
confidence: 87%
“…Although they are not complete yet, the genome projects of B. germanica [117] and P. americana [118] revealed that their repertoire of coding genes is larger than that of other related insects due to gene families' expansion, including some related to microbial defence and immune response. By integrating genomic and transcriptomic data, our group described 39 AMP-coding genes in B. germanica [119]. They belong to five families: defensins, termicins, drosomycins, attacins and blattellicins.…”
Section: Role Of the Host Immune System In The Symbiotic Interactionmentioning
confidence: 99%